EFEKTIVITAS SELF EFFICACY MENGAHADAPI BULLYING DI SEKOLAH: SELF-EFFICACY IN DEALING WITH BULLYING AT SCHOOL - Dewi Sri Anggraini; Maulidiyah Junnatul Azizah Heru; Atika Jatimi; Zainal Munir; Handono Fatkhur Rahman (Politeknik Kesehatan Kemenkes RI Jakarta I, 2020)
Introduction: Bullying behavior becomes an unsettling problem at school. bullying cases have a major impact on the psychology of victims of bullying. Improper coping relationships can form negative behaviors. This study aims to improve Self-efficacy which plays an important role in overcoming bullying events. Method: this study uses a literature review method by searching the electronic data base PROQUEST, EBSCO, DOAJ, GOOGLE SCHOLAR, GATE RESEARCH with keywords: self-efficacy, bullying, victim intimidation. Literatul review used as many as 20 articles in accordance with the inclusion criteria and exclusion criteria. Results: this study shows the effectiveness of self-bullying in schools, where self-efficacy is able to give an emphasis on individual self-ability to overcome the problem of bullying in school, so that bullying increases. Conclusion: bullying cases in schools can be agreed with the self-efficacy of each individual. self efficacy helps someone in overcoming the problem of bullying and using appropriate coping to solve the problem. Keywords: Self-efficacy, bullying, bullying victim at school